2018
DOI: 10.1039/c8dt02965b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, chemical characterization and cancer cell growth-inhibitory activities of Cu(ii) and Ru(iii) aliphatic and aromatic dithiocarbamato complexes

Abstract: The effects mediated by different cyclic dithiocarbamic ligands on three classes of antiproliferative coordination compounds were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…During the dithiocarbamate synthesis (Scheme (iv), Figure ), we observed that the nucleophilic attack of the glycosyl‐conjugated secondary amine toward CS 2 in water is slower (6 h) than the same process involving less sterically hindered alkyl amines as starting material (usually 1–2 h, for example, piperidine) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the dithiocarbamate synthesis (Scheme (iv), Figure ), we observed that the nucleophilic attack of the glycosyl‐conjugated secondary amine toward CS 2 in water is slower (6 h) than the same process involving less sterically hindered alkyl amines as starting material (usually 1–2 h, for example, piperidine) …”
Section: Resultsmentioning
confidence: 99%
“…Two main IR regions are taken into account when characterizing DTC derivatives, both ligand salts and metal–DTC complexes. First is the spectral region 1100–1550 cm −1 , in which the ν (N−CSS) band can be found and its position depends strongly on the extent of double bond character of the N−C bond . In the case of a single‐bond form, the band is located at 1250–1350 cm −1 , whereas it is found at higher wavenumbers (1640–1690 cm −1 ) if the DTC ligand contains a basically double C=N bond (thioureidic form) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations